A New Rat Model of Chronic Cerebral Hypoperfusion Resulting in Early-Stage Vascular Cognitive Impairment - Wang, Jinxin; Yang, Chenyi; Wang, Haiyun; Li, Dongxue; Li, Tang; Sun, Yi; Zhao, Mingshu; Ma, Ji; Hua, Wei; Yang, Zhuo (Frontiers in Aging Neuroscience, 2020)
Abstract Objective: Currently, most vascular dementia models are established by occluding one or both carotid arteries to reduce cerebral blood flow in order to mimic chronic cerebral hypoxia. Due to the sudden interruption of blood flow, the process of gradual narrowing of the carotid artery cannot be completely imitated. Therefore, this paper hopes to establish a model of bilateral carotid stenosis, with mild cognitive dysfunction and mild white matter changes to simulate patients with pre-vascular dementia. Method: Initially, aged (22-24 months) Wistar Rats were performed to bilateral CCA stenosis (BCAS) or occlusion (BCAO) or sham operation（Control group）. Cerebral blood flow (CBF) in the frontal cortices was measured by Doppler flowmetry. The cognitive function impairment was detected with the Morris Water Maze on the 30th after operation. Cerebral MRI was used by detecting the change of fractional anisotropy (FA) in rats to assess white matter injury on the 30th after operation. Histological studies were performed at 30 days after surgery. Results: The mortality is 11%（30/34）in the BCAS group. At 2 hours, the CBF values (ratio to the preoperative value) decreased significantly to 77.3±13.4% in the BCAS group, whereas 37.3±12.5% in the BCCA group. In BCAS groups, the microscopic structure changed slightly after 30 days in the CA1 hippocampus of rats. The difference between the escape latency in the BCAS model and control groups was less significant of that in the model group(P<0.5). HnRNPA2 found to be significantly declined in the hippocampus of BCAS group rats. The Gabbar-α1 decrease in BCAS group animals compared with control. Fluorescence staining of GFAP showed that the space of injured neurons was filled by stellate neuronal cells in the brain of the BCAS group. This phenomenon is more pronounced in the BCCA group. MRI study in the rat model of the BCAS model revealed the FA valve is slightly lower in hippocampal and cortex, the intense changes were more severe in BCCA rats. Conclusion: Severe bilateral carotid stenosis induced mild cognitive dysfunction slightly cerebral structural change in aged rats. Chronic cerebral hypoperfusion model in this study was established successfully.